PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MEDIA GAMBAR DI KELAS III SEKOLAH DASAR - Apriani, Ingga; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to implement learning and improve poetry writing skills using image media in class III of state Elementary School 35 Sepandan Sambas District. The method used in this research is a descriptive method. This form of research is class action research with 3 cycles of treatment with stages of planning, implementation, observation, and reflection. Results that want to be achieved is a valid data, accurate, accountable about the improvement of poetry writing skills using image media in class III of state Elementary School 35 Sepandan Sambas District that will be presented in the form of Data of research results. The research Setting is conducted in grade III of SD Negri 35 Sepandan Sambas District that will be presented in the form of Data of research results. The research Setting is conducted in grade III of SD Negri 35 Sepandan Sambas District. The results of his research are as follows: Increased teacher's ability to carry out cycle I study obtained on average 2.84, cycle II gained an average of 2.96, and cycle III was obtained on average 3.65. Increased student writing skills on the I cycle gained an average of 40.74, cycle II gained an average of 55.55, and cycle III gained an average of 76.29.Â Keywords: Enhancement, Media images, Poetry writing skills